Comorbid Diseases and Outcomes of Critically Ill COVID-19 Patients Admitted to an Indonesian Intensive Care Unit from May to October 2021 - Siahaan, Katrin Wilentina; Somia, I Ketut Agus; Utama, I Made Susila; Dian, Ni Made Dewi; Gayatri, Anak Agung Ayu Yuli; Purnamasidhi, Cokorda Agung Wahyu; Merati, Ketut Tuti Parwati (Universitas Airlangga, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2). The spread of COVID-19 has become a worldwide health threat, with 583,038,110 cases and a death toll of 6,416,023. This study attempted to determine the relationship of age, sex, and comorbid diseases with the outcomes of critically ill COVID-19 patients at Prof. Dr. IGNG Ngoerah Central General Hospital, Denpasar, Indonesia. Methods: This analytic study employed a retrospective approach, analyzing secondary data from medical records using a purposive sampling method. The research included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using a general linear model performed with the assistance of IBM SPSS Statistics for Windows, version 23.0 (IBM Corp., Armonk, N.Y., USA). A statistical analysis result with a p-value of less than 0.05 was deemed significant. Results: A total of 264 critically ill COVID-19 patients were hospitalized in the Intensive Care Unit of Prof. Dr. IGNG Ngoerah Central General Hospital from May to October 2021. Comorbid diseases were present in 215 patients. The comorbid diseases that had the greatest impact on increasing mortality were diabetes mellitus, hypertension, kidney disease, and cardiovascular disease (p=0.000–0.006, 95% CI). Conclusion: Age and sex do not have any significant relationship with the outcomes of critically ill COVID-19 patients. Meanwhile, comorbid diseases, such as diabetes mellitus, hypertension, and renal and cardiovascular diseases, pose a significant impact on the mortality rate of critically ill COVID-19 patients. Highlights: 1. This study investigated patients who were critically ill with COVID-19 to determine the relationship between age, sex, comorbidities, and patient outcomes. 2. The findings of this study may provide additional data on the impact of comorbidities on the severity of COVID-19, which can be valuable to prevent mortality due to the infection.